2018
DOI: 10.3389/fnagi.2017.00445
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular and Periventricular Anomalies in the Aging and Cognitively Impaired Brain

Abstract: Ventriculomegaly (expansion of the brain’s fluid-filled ventricles), a condition commonly found in the aging brain, results in areas of gliosis where the ependymal cells are replaced with dense astrocytic patches. Loss of ependymal cells would compromise trans-ependymal bulk flow mechanisms required for clearance of proteins and metabolites from the brain parenchyma. However, little is known about the interplay between age-related ventricle expansion, the decline in ependymal integrity, altered periventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 73 publications
3
23
0
2
Order By: Relevance
“…3A,B). Semi-automated segmentation using ITK-SNAP (Shook et al, 2014;Snippert et al, 2010;Todd et al, 2017;Yushkevich et al, 2006) followed by 3D reconstruction of the lateral ventricles and whole brain using 3D Slicer (Acabchuk et al, 2015;Shook et al, 2014) revealed that the average total brain volume increases rapidly from 15 gw to 1 year. Regression analysis predicts that from 19 gw to birth, the brain grows at a nearly linear rate of 1.2×10 6 mm 3 /year (23 cm 3 /week) and from birth to 1 year at 5.5×10 5 mm 3 /year (11 cm 3 /week) (see also Kinoshita et al, 2001).…”
Section: Human Lateral Ventricle Volume and Surface Area Changes Corrmentioning
confidence: 99%
See 2 more Smart Citations
“…3A,B). Semi-automated segmentation using ITK-SNAP (Shook et al, 2014;Snippert et al, 2010;Todd et al, 2017;Yushkevich et al, 2006) followed by 3D reconstruction of the lateral ventricles and whole brain using 3D Slicer (Acabchuk et al, 2015;Shook et al, 2014) revealed that the average total brain volume increases rapidly from 15 gw to 1 year. Regression analysis predicts that from 19 gw to birth, the brain grows at a nearly linear rate of 1.2×10 6 mm 3 /year (23 cm 3 /week) and from birth to 1 year at 5.5×10 5 mm 3 /year (11 cm 3 /week) (see also Kinoshita et al, 2001).…”
Section: Human Lateral Ventricle Volume and Surface Area Changes Corrmentioning
confidence: 99%
“…Regions corresponding to the LGE in fetal tissue and the lateral wall of the lateral ventricle in postnatal tissue were dissected and sectioned coronally at 100 mm thickness. Immunohistochemistry was performed as described (Todd et al, 2017) using the following antibodies: goat polyclonal anti-GFAP (1:250; Abcam, #ab53554), mouse monoclonal anti-FOXJ1 (1:250; Invitrogen, #14-9965-80), guinea pig anti-doublecortin (DCX) (1:1000, EMD Millipore, #AB2253) and rabbit anti-Ki67 (1:1000; Novocastra, #6013874). Alexa Fluor dye-conjugated polyclonal secondary antibodies (1:500) were used: donkey anti-mouse 405 (Abcam, #ab175658), donkey anti-mouse 488 (Invitrogen, #21202), donkey antirabbit 546 (Invitrogen, #A10040), donkey anti-goat-647 (Invitrogen, #A21447) and donkey anti-rat 647 (Invitrogen, #A18744).…”
Section: Human Brain Tissue Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Роль эпендимоцитов в нейрогенезе В последние годы достаточно широко обсуждается вопрос участия эпендимальных клеток в нейрогенезе. Однако факт того, что в боковых желудочках взрослого человека отсутствуют эпендимальные клетки, позволяет предположить, что эпендимоциты в нейроге-ОБЗОРНЫЕ СТАТЬИ ® незе участвуют ограниченно, только во внутриутробном периоде развития ЦНС [17][18][19][20].…”
Section: Review Articles фундаментальная и клиническая медицина ®unclassified
“…The choice of LV volumes is further supported by studies describing the brain’s fluid-filled ventricles as a biomarker of the aging brain [2729], and studies linking age-related ventricular expansion to changes in cognitive function at a subject-specific level [3032]. A study by Todd et al [33] showed a strong linear relationship between LV volume expansion and worsening of cognitive performance over a two-years period. The study assessed cognitive function by tests primarily designed to reveal symptoms of major neurocognitive disorders.…”
Section: Introductionmentioning
confidence: 99%